Strategies for successful animal shelters - Reese, Laura A. (Laura Ann), 1958- (Academic Press, 2019)
Strategies for Successful Animal Shelters is the first book to assess the relationship between shelter traits, activities and critical outcome variables, such as live release or save rates. This book provides a data-based evaluation of shelter processes and practices with explicit recommendations for improved shelter activities. Using a survey of licensed animal shelters, case studies, and data on state inspections, complaints, and save rates, this book provides an assessment of the activities, processes, and procedures that are most likely to lead to positive outcomes for a variety of animal shelters. The book also contributes to community debate around animal sheltering and provides best practices, methods and means to assess local shelters to ensure the highest level of animal welfare. It is a valuable resource for animal shelter professionals and rescue groups, as well as students in disciplines such as animal science, animal welfare and shelter medicine.